Interindividual differences in parameters of the EEG and HRV in the humans with various levels of the entropy of EEG, HRV, immunocytogram and leukocytogram - Zukow, W; Popadynets’, O O; Gozhenko, A I; Popovych, I L (Journal of Education, Health and Sport, 2019)
Background. Previously, we have shown that the entropy of the normalized parameters of the HRV and spectral power density (SPD) of loci of EEG significantly correlate with the entropy and parameters of immunity, which testifies to their modulating regulatory effects. Individual analysis revealed that the entropy of HRV and EEG as well as Immunocytogram and Leukocytogram is characterized by considerable variability. The method of cluster analysis was the distribution of the observed contingent into four groups that are homogeneous in terms of entropy. The purpose of this study is to identify the spectral parameters and indices of HRV, the amplitude-frequency and spectral parameters of the rhythms of EEG as well as the indices of asymmetry and lateralization of rhythms, which together are four clusters of entropy significantly different from each other. Material and methods. In basal conditions in 37 men and 14 women with chronic pyelonephritis and cholecystitis in remission as well as without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism, we recorded twice, before and after balneotherapy at the spa Truskavets’, EEG (“NeuroCom Standard”) and HRV (“Cardiolab+VSR”). Than we calculated for each locus of EEG and HRV the Entropy of normalized SPD using Shannon’s formula. Results. As a result of screening relationships between the normalized EEG entropy levels on the one hand, and the EEG and HRV parameters and indices on the other, three pairs of quasi-mirror patterns were detected. According to the results of the discriminant analysis 37 parameters were identified as characteristic of the entropy clusters, 11 of which relate to delta rhythm, 8 to theta rhythm, 8 to beta rhythm and 4 to alpha rhythm of EEG, 6 more represent HRV. Conclusion. The entropy clusters of SPD of EEG that we have discovered previously are quantitatively and qualitatively distinct from each other by at least 37 amplitude-frequency and spectral parameters of EEG as well as of HRV.